Environmental preservation and the Grey Cliffs conflict : negotiating common narratives, values, and ethos - Pickering, Kristin D. (Logan : Utah State University Press, 2024)
"A qualitative, ethnographic, observational case study approach presenting an analysis of the process of conflict negotiation between an Army Corps of Engineers Resource Manager and a community as they struggle to address a deteriorating, Corps-managed recreational lake area"--
The Grey Cliffs conflict : situating the issues -- Narratives, stories, ethos building, and environmental justice -- Community narratives and ethos : agency and values -- Motivating the compliant individual : a Corps Resource Manager's rhetoric of regulation -- Attempting to persuade a community organizer : Norma's narrative of logic without emotion -- A Corps Resource Manager's rhetoric of relationship : co-constructing ethos with a community -- Narratives of jointly accomplished, social action through aligned values : the negotiated resolution -- The continued negotiation process : implications for the future.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 28, 2024).
JSTOR
Keywords: United States. -- Army. -- Corps of Engineers; United States. -- Army. -- Corps of Engineers; Conflict management -- Tennessee -- Case studies; Communication -- Social aspects -- Tennessee -- Case studies; Environmental protection -- Social aspects -- Tennessee -- Case studies; Environmental management -- Tennessee -- Case studies; Gestion des conflits -- Tennessee -- Études de cas; Environnement -- Protection -- Aspect social -- Tennessee -- Études de cas; Environnement -- Gestion -- Tennessee -- Études de cas; Environmental Conservation & Protection; NATURE; Technical Writing; TECHNOLOGY & ENGINEERING; Communication -- Social aspects; Conflict management; Environmental management; Environmental protection -- Social aspects; Tennessee; Electronic books; Electronic books; Case studies